Fitzmaurice Voicework Pilot Study with fMRI. Issue 2 (4th May 2019) - Watson, Lynn; Hirshorn-Johnston, Rachel; O'Bryan, Sean R.; Davis, Tyler
ABSTRACT: Fitzmaurice Voicework (FV) is a voice training methodology used by performing artists and in corporate and clinical settings. Although little quantitative research has been done on FV, reports from practitioners suggest that it may enhance cognitive control during performance. The present study used neuroimaging to investigate the neurobiological effects of FV. Ten FV-certified teachers participated in a pilot study in which they were scanned pre- and post-FV Destructuring/tremoring (DsT) and gentle aerobics. In resting state scans, greater connectivity was observed between the right executive control network (RECN) and the language network post-FV DsT relative to gentle aerobics, whereas RECN connectivity between anterior salience and visuospatial networks was reduced. During a category learning test, right dorsolateral prefrontal cortex (part of RECN) activation on correct trials was greater for post-FV DsT compared to pre-FV DsT. Together, these results suggest that FV could impact executive cognitive control networks in the brain, corroborating reports from practitioners, suggesting a locus for potential therapeutic effects, and securing critical pilot data necessary to support further (and larger) studies.